Islamic Boarding Schools and Da'wah of Religious Moderation - Ahmad Shofi Muhyiddin (UIN Antasari Banjarmasin, 2023)
This study discusses the da'wah of religious moderation carried out by the Edi Mancoro Islamic boarding school through the internalization of religious moderation values in the Islamic boarding school environment and the surrounding community. The presence of Islamic boarding school as an indigenous da'wah institution should be at the forefront in instilling wasaṭiyah values in all da'wah activities, bearing in mind that the Indonesian nation is a multicultural nation. This type of research is field research using a qualitative analysis approach with the Miles and Huberman analysis model. The research was conducted at the Edi Mancoro Islamic boarding school in April-July 2022. The results of this study found the values of religious moderation in the Edi Mancoro Islamic boarding school, including: firstly, the concept of Islamic normative spiritual values which includes: the value of qana'ah (accept what existence) and the value of tawadhu' (humble). Secondly, the concept of the value of nationalism commitment which is embodied by: the value of love for the motherland and the value of mutual cooperation. Thirdly, social values which include: the value of social sensitivity and the value of compassion between religious communities. The values of religious moderation are internalized by going through 3 stages, including: the value transformation stage, the value transaction stage and the transinternalization stage. Finally, the model of da'wah of religious moderation used by the Edi Mancoro Islamic Boarding School in Semarang Regency includes: da'wah of Madrasa model, da'wah of yellow book's halaqah model, da'wah of uswah model, and da'wah of interreligious cooperation model which is realized through cooperative da'wah in inter-religious dialogue, cooperative da'wah in interfaith joint prayer forums and cooperative da'wah in religious